Extraction And Curcuminoids Activity From The Roots Of Curcuma Longa By Rslde Using The Naviglio Extractor - Cozzolino, Imma; Vitulano, Manuela; Conte, Esterina; D’Onofrio, Francesca; Aletta, Lorenzo; Ferrara, Lydia; Andolfi, Anna; Naviglio, Daniele; Gallo, Monica (European Scientific Journal, ESJ, 2016)
In the present study the extraction of curcuminoids was performed from Curcuma longa roots, focusing the interest on curcumin, the major phenolic component of the root that has been shown to have a high antioxidant activity. A cold extraction technique was employed as an alternative to other conventional solid-liquid extraction techniques such as maceration, infusion, percolation and extraction with Sohxlet which expose curcuminoids to light, heat and oxygen causing the degradation and thus limiting the effectiveness of the processes themselves. The Naviglio Extractor (NE) or rapid solid-fluid dynamic extraction (RSLDE) is an innovative technology of solid-liquid extraction that can extract in a short time, compared to other existing techniques, bioactive substances present in the solid matrix using water as solvent, at room temperature. Curcumin is a plant pigment of very bright yellow orange color and is referred to as the E100 in the list of accepted color additives in the food and pharmaceutical sector being devoid of toxicity. In the Indian and Asian cuisine it is used to prepare the curry and various typical local sauces while in the Ayurvedic medicine for many centuries to treat a variety of ailments. Recent studies have shown that curcumin exerts anti-tumor effects for its ability to induce apoptosis in cancer cells without cytotoxic effects on healthy cells; in fact, it can interfere with the activity of the transcription factor ï¡ and ï¢-TNF (Tumor Necrosis Factor) which has been linked to a number of inflammatory diseases and cancer diseases.